UJI EFEKTIVITAS Trichoderma spp. UNTUK MENEKAN PERKEMBANGAN JAMUR Ganodermaboninense Pat. PADA MEDIA PELEPAH KELAPA SAWIT - Purwanto, Moh. Intim; Lakani, Irwan; Asrul, Asrul (AGROTEKBIS, 2016)
Stem rot in oil palm crops caused by fungal infections Ganoderma boninense which is an important disease that attacks the oil palm plantations. This study aims to determine how the provision of Trichoderma spp. and the amount of inoculum best in suppressing the growth of Ganoderma boninense on palm midrib media. The research was conducted in the laboratory of fitopathology Unit of the Faculty of Agriculture, Tadulako University, Palu. This study was prepared using completely randomized design (CRD) with 2 factors. The first factor is the way the provision of Trichoderma spp. The second factor is the amount of inoculum repeated 4 times. The data were followed by HSD test at 5%. The results showed that of the statistical analysis are interactions between granting Trichoderma spp. and the amount of inoculum in suppressing the growth of G. boninense on palm midrib media. Where is the best interaction contained in the application Trichoderma spp. before inoculation G. boninense with a concentration of 8 g. Applications Trichoderma spp. led to the emergence of different basidiokarp, basidiokarp emergence longest time in the application of Trichoderma spp. with a concentration of 8 g ie 35.00 days, but not different with other applications, but in contrast to controls.Â Key Words : Concentration, G. boninense Pat., palm midrib media, Trichoderma spp.